Analisis Kualitas Pelayanan Farmasi Rawat Jalan Terhadap Kepuasan Pasien RSI Ibnu Sina Simpang Empat - Assyahri, Wahib; Hasbullah, Rizan; Putri Oktaviane, Diga; Vaguita, Mercya (Laboratorium Jurusan Ilmu Administrasi Negara Fakultas Ilmu Sosial Universitas Negeri Padang, 2025)
This study examines the problems of pharmaceutical services at the Ibnu Sina Simpang Empat Hospital Pharmacy, focusing on analyzing service quality in relation to patient satisfaction. The main problems identified include long waiting times for medication (2-3 hours), unavailability of medication, and inadequate waiting facilities, which have an impact on patient dissatisfaction. The purpose of this study was to evaluate service quality based on the five dimensions of SERVQUAL (tangibility, reliability, responsiveness, assurance, and empathy) in explaining patient satisfaction. The research method used a descriptive quantitative approach with a questionnaire as the main instrument, involving 370 patient respondents using simple random sampling. Based on the results of the study on the quality of pharmaceutical services at the Ibnu Sina Simpang Empat Hospital Pharmacy, it can be explained that in general, the quality of service is considered very good with an average score of 4.26. The best service dimensions were empathy (score of 4.30) and reliability (score of 4.29), indicating that pharmacy staff demonstrated a friendly attitude, effective communication, and adequate technical competence. However, this study also revealed several critical issues that need attention, particularly regarding drug availability, which only scored 3.93, and service waiting time, which scored the lowest at 3.71 in terms of assurance. This study recommends improvements in drug stock management, adding staff during peak hours, and upgrading waiting room facilities to increase patient satisfaction. These findings provide practical contributions for hospitals in optimizing patient-centered pharmacy services.